An affordable efficient SrWO4 decorated Bi2O3 nanocomposite: Photocatalytic activity for the degradation of methylene blue under visible light irradiation. (2022) - Subalakshmi, A.; Kavitha, B.; Srinivasan, N.; Rajarajan, M.; Suganthi, A.
Abstract: The SrWO4 /Bi2 O3 nanocomposite was gotten by co-precipitation process and described by X-ray diffraction (XRD), UV–vis diffuse reflectance spectroscopy (UV–vis DRS), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), high resolution transmission electron microscopy (HR-TEM), energy dispersive X-ray analysis (EDX), Thermal gravimetric analysis (TGA) and Raman spectroscopy estimations. Average crystallite sizes calculated by XRD are 33 nm for Bi2 O3 and 29 nm for SrWO4 changed Bi2 O3 . The visible light photocatalytic action of the synthesized nanocomposite was assessed by the methylene blue (MB) degradation in visible illumination irradiation. SrWO4 / Bi2 O3 have enhanced photocatalytic action for the degradation of MB when contrasted with that of Bi2 O3 and SrWO4 . Maximum degradation of 99% was accomplished with SrWO4 / Bi2 O3 concentration of 0.1 g/L, initial concentration of 10 µM of MB and 180 min illumination time. The improved photocatalytic activity of the nanocomposite was credited to successful electron–hole division.